Approaches to Paul: a student's guide to recent scholarship - Zetterholm, Magnus (Fortress Press, 2009)
What distinguishes the "new perspective on Paul" - and what lies beyond it? What are scholars saying about Paul and the Roman Empire or about the intersection between feminist and postcolonial interpretation of Paul? Magnus Zetterholm provides a clear and reliable guide to these and other lively issues in the contemporary study of Paul, surveying the history of the principal perspectives on Paul's relation to Judaism and the Jewish law and showing the relationships between answers given to those questions and the assumptions scholars bring to other issues as well. This is an indispensable handbook for the beginning student of the apostle and his thought.